Simulation and experimental study of parameters in centrifugal electrospinning: Effects of rotor form on fiber formation. Issue 38 (2nd August 2022) - Wang, Han; Feng, Liang; Zeng, Jun; Chen, Lingmin; Chen, An; Liu, Maolin; Xiong, Jingang
Abstract: Nanofiber is a kind of high‐performance material, which has great applications. Among many preparation methods, centrifugal electrospinning combines the advantages of electrospinning and centrifugal spinning, with high yield and a wide range of application. But its influencing factors are numerous, the process is still immature, and unable to meet the needs of industrialization. Here, we design a set of centrifugal electrospinning equipment and its process, and explore the influence of rotor form on fiber formation. First, the structure and working principle of experimental equipment of centrifugal electrospinning are introduced. Then, the influence of two factors, the rotor shape and rotor material, on space electric field is studied through theoretical and simulation analysis. Finally, based on the designed equipment, the effects of different rotor forms on the fibers preparation of centrifugal electrospinning are studied. The results show that the fiber diameter of centrifugal electrospinning is greatly affected by the form of the rotor. By changing the surface shape of the rotor and the rotor material, the diameter of the fiber can be controlled. Experiments show that the average fiber diameter of the γ‐shaped rotor is the smallest, and the fiber spun with ULTEM PEI 1010 material has the best overall performance. Abstract : Electrostatic dissipation affects the fiber diameter of centrifugal electrospinning.